Integrated structure-guided computational design of novel substituted quinolizin-4-ones as Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH) inhibitors. (December 2022) - Vyas, Vivek K.; Shukla, Tanvi; Tulsian, Kartik; Sharma, Manmohan; Patel, Shivani
Abstract: Plasmodium falciparum dihydroorotate dehydrogenase ( Pf DHODH) is a known drug target for the development of antimalarial agents. Herein, we presented integrated structure-guided computational strategies for the design of novel quinolizin-4-ones as Pf DHODH inhibitors. PROCHECK and ERRAT analysis were performed for the validation of co-crystal structures of Pf DHODH enzyme bound to the inhibitors available on PDB. Based on the results, PDB ID: 6i55 was selected for further structure-guided in silico studies. Five featured-based pharmacophore model (AADRR) was generated, and validated using GH scoring (0.74) and ROC analysis (0.94). Validated structure-based model was further used as a 3D search query to screen the ZINC database. Retrieved database compounds ZINC00386658, ZINC08439293, and ZINC09089086 were found in agreement with query features based on their highest fitness scores. HTVS, SP and XP docking studies with these retrieved hits demonstrated important interactions (His185. Arg265) with Pf DHODH. Mapping of features of the pharmacophore model on these retrieved hits along with the role played by scaffolds and functional groups in docking study helped in the selection of quinolizin-4-one as a main scaffold and different functional groups for the design of novel compounds as Pf DHODH inhibitors. In silico ADMET prediction study suggested that designed quinolizin-4-ones are "drug-like" candidates and can be synthesised without too many difficulties. In docking study of newly designed compounds, 8d exhibited the highest docking score of − 12.78 kcal/mol and formed important polar interactions (His185. Arg265) with the Pf DHODH. Pf DHODH-8d complex showed stable RMSD between 2.5 Å and 3 Å during 100 ns MD simulation study. The RMSD, RMSF and RoG analysis of the Pf DHODH-8d complex indicated the absolute stability of the complex. Overall, combined in silico study identified quinolizin-4-ones as selective Pf DHODH inhibitors. Graphical Abstract: ga1 Highlights: Structure-guided pharmacophore modelling provided five feature-based pharmacophore model. Quinolizin-4-one as a core and other substituents on quinolizin-4-one were selected as per the structure-guided modelling. Designed compounds formed significant polar interactions with Arg265 and His185 in the docking study. ADMET prediction study revealed that designed compounds possess drug likeness and lead likeness characteristics. MD simulations explored the binding conformations of the ligand with Pf DHODH and measured the stability of the complex.